Preparation and electrical characterization by Impedance Spectroscopy of PVC+LiCF3S03+Ti02 nanocomposite polymer electrolytes / Norhafiza Muda - Muda, Norhafiza (2007)
Nanocomposite polymer electrolyte were prepared by combining PVC as a host polymer, lithium triflate, UCF3SO3 as doping salt and titanium dioxide, Ti02 as filler with a different ratio. All the films were prepared by solution casting technique. The ionic conductivity of the films of at room temperature was determined by Impedance Spectroscopy technique. The ionic conductivity of pure PVC was 1.04 x 10ˉ¹º Scmˉ¹. The highest ionic conductivity of PVC + LiCF3SC>3 films determined was 1.017 x 10ˉ⁷ Scmˉ¹ for 40 wt % of UCF₃SO₃. This ratio was used further for the preparation of PVC+LiCF3S03+Ti02 films by adding different ratio of Ti0₂ filler. The highest ionic conductivity of PVC+LiCF3S03+Ti02 film was 1.2556 x 10ˉ⁵ Scm⁻¹ at 8 wt % of TiC₂. The ionic conductivity of nanocomposite polymer electrolyte increased from 10ˉ⁷ to 10ˉ⁵ Scmˉ¹. The ionic conductivity of PVC significantly increased by the addition of salt and filler.